Some Physical and Engineering Properties of Black Cumin (Nigella sativaL.) Seed - CETIN, M.; YALCIN, I.; SIMSEK, E. (Asian Journal of Chemistry, 2010)
The physical and engineering properties of black cumin seed were determined as a function of moisture content in the range of 6.94 to 18.22 % dry basis. The average length, width and thickness were 3.19, 1.62 and 1.08 mm, at a moisture content of 6.94 % dry basis, respectively. In the moisture range from 6.94 to 18.22 % dry basis, studies on rewetted black cumin seed showed that the thousand seed mass increased from 2.99 to 3.17 g, the projected area from 2.13 to 3.35 mm2, the sphericity from 0.557 to 0.566, the porosity from 46.88 to 49.28 % and the terminal velocity from 5.11 to 5.60 m s-1. The bulk density decreased from 564.48 to 533.37 kg m-3 and the true density from 1062.75 to 1051.53 kg m-3 with an increase in the moisture content range of 6.94-18.22 % dry basis. The static coefficient of friction of black cumin seed increased linearly against surfaces of four structural materials, namely, rubber (0.265 to 0.334), aluminium (0.228 to 0.288), stainless steel (0.172 to 0.251) and galvanised iron (0.247 to 0.307) as the moisture content increased from 6.94- 18.22 % dry basis.